2006
DOI: 10.1007/s11664-006-0310-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stable Ge/Cu/Ti ohmic contacts to n-type GaN

Abstract: The performance of a novel Ge/Cu/Ti metallization scheme on n-type GaN has been investigated for obtaining thermally and electrically stable low-resistance ohmic contacts. Isochronal (2 min.) anneals in the 600-740°C temperature range and isothermal (690°C) anneals for 2-10 min. duration were performed in inert atmosphere. For the 690°C isothermal schedule, ohmic behavior was observed after annealing for 3 min. or longer with a lowest contact resistivity of 9.1 3 10 À5 V cm 2 after the 10 min. anneal for a net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…This turns out to be consistent with what Ponon et al found [32]. For convenience of comparison, the properties of several Cu-based ohmic contact stacks are tabulated [23][24][25][26] in table 1 , from which one sees that the ρ C value for the Ti/TiN/Cu being studied here is quite compelling. The leakage current characteristics are presented in figure 6 for different samples.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…This turns out to be consistent with what Ponon et al found [32]. For convenience of comparison, the properties of several Cu-based ohmic contact stacks are tabulated [23][24][25][26] in table 1 , from which one sees that the ρ C value for the Ti/TiN/Cu being studied here is quite compelling. The leakage current characteristics are presented in figure 6 for different samples.…”
Section: Resultssupporting
confidence: 86%
“…As a measure to avoid the Al-Au alloying problems, replacing Au with Cu in the so-called Cu-based contact alternatives has gained popularity [23,24]. Several approaches, such as Ge/Cu/Ti [25], Si/Ti/Al/Cu [23], Ti/Al/Ni/Cu [24], Ti/Al/TiN/Cu [26], have all been investigated. Some of the additional advantages of using Cu are for its lower bulk electrical resistivity (∼1.7 µ Ω cm) [27][28][29] as compared to Au's ∼2.2 µ Ω cm, and higher thermal conductivity (385 vs 310 W m −1 K) beside the lower cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] An effective diffusion barrier to Cu is thus required, especially for the ohmic contact. A few ohmic contact structures for GaN devices, such as Si/Ti/Al/Cu/Au, 14 Ge/Cu/Ge, 15 and Ti/Cu/Ge, 16 have been investigated. Although ohmic contacts could be achieved at relatively lower temperatures (<800 C) for these structures, they all suffer from having high contact resistance (r c > Â 10 -5 ohm cm 2 ).…”
mentioning
confidence: 99%
“…Thin lms of metal germanides are of considerable interest to be integrated into very large scale integration (VLSI) circuits as interconnects or ohmic contacts not only for Si and Ge based electronic devices but also for other alternative compound semiconductors. [1][2][3][4][5][6][7][8][9][10][11][12] This is primarily due to their low resistivity, good thermal stability and resistance to oxidation. Among the transition metal germanides, CoGe 2 has been well studied by many researchers for Ge based technology and scarcely for other semiconductor substrates.…”
Section: Introductionmentioning
confidence: 99%